Local dynamics in the Syrian conflict: Homegrown links in rebel areas blunt Jihadist ascendency - Khaled Yacoub Oweis (Stiftung Wissenschaft und Politik (SWP), 2016)
The Assad family reign has been marked by the ubiquitous intrusion of the Alawite-dominated security apparatus on the micro-level. The demise of the regime's vast network of repression in many regions has resulted in local patterns of governance, restoring or generating old and new elites. With the jihadist ascendency, many of the emerging structures have been smothered by religious ideology. Yet, under the surface, local power has been shaped by area-specific relationships and embedded cultures. Support from Western actors has increasingly focused on local actors who are seen as being opposed to the Islamic State or al-Qaeda. Without a fundamental change in the nature of the regime, however, prospects for harnessing such local dynamics for the larger objective of stabilization will remain limited. (SWP Comments)
Keywords: 320